2020
DOI: 10.1002/cyto.a.24221
|View full text |Cite
|
Sign up to set email alerts
|

Lymph Liquid Biopsy for Detection of Cancer Stem Cells

Abstract: Collection of a blood sample defined by the term “blood liquid biopsy” is commonly used to detect diagnostic, prognostic, and therapeutic decision‐making markers of metastatic tumors including circulating tumor cells (CTCs). Many tumors also release CTCs and other markers into lymph fluid, but the utility of lymphatic markers largely remains unexplored. Here, we introduce lymph liquid biopsy through collection of peripheral (afferent) and central (thoracic duct [TD]) lymph samples and demonstrates its feasibil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Some tumor cells infiltrate into the lymphatic vessels and then colonize distant organs or tissues through the lymphatic circulation and continue to grow into metastases [ 32 ]. Han et al [ 33 ] detected stem-like lymphatic circulating tumor cells from the thoracic duct that empties lymph directly into the circulation, suggesting a key role for the lymphatic system in mediating distant metastasis of cancer. The relationship between lymph node and distant metastasis has also been demonstrated in mouse cancer models by injecting tumor cells directly into lymphatic vessels and using photoswitchable tumor cell models [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some tumor cells infiltrate into the lymphatic vessels and then colonize distant organs or tissues through the lymphatic circulation and continue to grow into metastases [ 32 ]. Han et al [ 33 ] detected stem-like lymphatic circulating tumor cells from the thoracic duct that empties lymph directly into the circulation, suggesting a key role for the lymphatic system in mediating distant metastasis of cancer. The relationship between lymph node and distant metastasis has also been demonstrated in mouse cancer models by injecting tumor cells directly into lymphatic vessels and using photoswitchable tumor cell models [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The utilization of the liquid biopsy approach represents the optimal solution for addressing this challenge. Liquid biopsy is a practical method used to detect and isolate CTCs from a patient's whole blood, which can provide critical information regarding tumor personalized features, development, and progression [53,54]. It has been reported that CTC populations in patients demonstrate the same heterogeneity as the tumors from which they originate [55].…”
Section: Single-cell Transcriptomics For Detecting and Targeting The ...mentioning
confidence: 99%
“…Other studies indicate that systemically infused MSCs can be found in secondary lymphoid organs [e.g., mesenteric lymph nodes after intracardiac infusion (Li et al, 2012), lymph nodes, Peyer patches, spleen (Schwarz et al, 2014)]. Interestingly, Han et al (2020) very recently reported the presence of lots of circulating cells able to form spheroids in the thoracic duct of a mouse model of melanoma, though distant metastases were not developed. Altogether, those data suggest that as cancer cells do, MSCs may exploit several bodily fluid systems as natural transportation routes (Follain et al, 2020; Figure 1).…”
Section: What If Not Just the Blood?mentioning
confidence: 99%